PENGARUH BOOK-TAX DIFFERENCE, ARUS KAS OPERASI, ARUS KAS AKRUAL, DAN UKURAN PERUSAHAAN PADA PERSISTENSI LABA - Dewi, Ni Putu Lestari; Putri, I.G.A.M Asri Dwija (E-Jurnal Akuntansi, 2015)
The purpose of this study was to determine the effect of book-tax difference based on permanent and temporary differences, operating cash flow, acrruals cash flow and firm size on earnings persistence. The population used was Hospitality and Tourism company listed on the Indonesia Stock Exchange. Based on purposive sampling method, the sample amounted to 14 companies with the observation period 2009-2011. The analysis technique used is multiple regression analysis. The conclusion is that the temporary differences, permanent differences, operating cash flow and firm size has positive effect on earnings persistence, while accruals cash flow has no effect on earnings persistence.
Keywords: book-tax difference, operating cash flow, cash flow accruals, firm size